Vision 2030 Jamaica : national development plan : the popular version (Planning Institute of Jamaica KingstonJM, 2010)
Presents key areas for development, highlights major challenges, includes strategies, programmes and projects to achieve long-term goals.
Keywords: DEVELOPMENT PLANS